Effects of singlet oxygen generated by a broad-spectrum viral fusion inhibitor on membrane nanoarchitecture - Hollmann, Axel (Nanomedicine, 2015)
Targeting membranes of enveloped viruses represents an exciting new paradigm to explore on the development of broad-spectrum antivirals. Recently, broad-spectrum small-molecule antiviral drug were described, preventing enveloped virus entry at an intermediate step, after virus binding but before virus–cell fusion. Those compounds, including an oxazolidine-2,4-dithione named JL103 that presented the most promissing results, act deleteriously on the virus envelope but not at the cell membrane level. In this work, by using atomic force microscopy (AFM), we aimed at unraveling the effects that JL103 is able to induce in the lipid membrane architecture at the nanoscale. Our results indicate that singlet oxygen produced by JL103 decreases membrane thickness, with and expansion of the area per phospholipid, by attacking the double bonds of unsaturated phospholipids. This membrane reorganization prevents the fusion between enveloped virus and target cell membranes, resulting in viral entry inhibition.